The innkeeper's sister - Goodnight, Linda (Goodnight, Linda. Honey Ridge novel, 2017)
Grayson Blake always has a purpose- and never a moment to lose. He's come home to Honey Ridge to convert a historic gristmill into a restaurant, but his plans crumble like Tennessee clay when the excavation of a skeleton unearths a Civil War mystery- and leads him back to a beautiful and familiar stranger. Once a ballet dancer, now co-owner of the Peach Orchard Inn, Valery Carter harbors pain as deep as the secrets buried beneath the mill. A bright facade can't erase her regrets any more than a glass of bourbon can restore what she's lost. But spending time with Grayson offers Valery a chance to let go of her past and imagine a happier future. And with the discovery of hidden messages in aged sheet music, both their hearts begin to open. Bound by attraction, and compelled to resolve an old crime that links the inn and the mill, Grayson and Valery encounter a song of hurt, truth- and hope.